Prototipe Knowledge Management System Sebagai Media Pembelajaran Distance Learning Dengan Pendekatan SECI Dan MVC - Endah Wiji Lestari (LPPM Universitas Bina Sarana Informatika, 2018)
STMIK Cikarang is an educational institution with teaching experience (tacit) teaching. Tacit is owned by teachers or lecturers poured or documented on teaching materials or explicit knowledge materials such as modules, slides, ltm, syllabus and sap. Transfer of knowledge done by lecturers or lecturers with students should be done in a discussion forum which at this time does not exist yet and can not be uploaded or downloaded by the students. Knowledge management system as learning distance learning media is an effective way to overcome the problem of sharing and transfer of knowledge in STMIK Cikarang. System development method used is prototyping model. Validation test using Focus Group Discussion. Software quality is tested by adopting 4 charteristics of ISO 9126 with characteristics of functionality, reliability, usability, and efficiency. The results obtained from this research is Prototype KMS as a learning media distance learning based website that can be applied well with good quality testing so it can be a solution to improve mastery of knowledge in teaching and learning activities. Evidenced by the results of software testing with the adoption of 4 karasteristik ISO 9126 with the aspect of functionality generate percentage of 80.42% with good criteria, then the reliability aspects with percentage of 79.56% with good criteria, usability aspect with the percentage of 83.17% with good criteria and efficiency aspect with percentage 86,89% with very good criterion. Of the total test with all four aspects, the respondents generated 83.51% with good criteria. Key Word: Knowledge Management System, Distance learning, SECI Model, Prototyping Model, Focus Group Discussion, ISO 9126, Website Based